Synthesis and evaluation of a boronate-tagged 1, 8-naphthalimide probe for fluoride recognition. Issue 14 (17th December 2014) - Xu, Su-Ying; Sun, Xiaolong; Ge, Haobo; Arrowsmith, Rory L.; Fossey, John S.; Pascu, Sofia I.; Jiang, Yun-Bao; James, Tony D.
Abstract : A biocompatible fluoride receptor has been developed where the interaction between the boronic acid ester and amine (NH) results in fluoride ion selectivity and enhanced fluorescence quenching. Abstract : A biocompatible fluoride receptor has been developed where the interaction between the boronic acid ester and amine (NH) results in fluoride ion selectivity and enhanced fluorescence quenching.